The capacity for thermal protection of photosynthetic electron transport varies for different monoterpenes in Quercus ilex (PLANT PHYSIOLOGY, 2005)
Heat stress resistance of foliar photosynthetic apparatus was investigated in the Mediterranean monoterpene-emitting evergreen sclerophyll species Quercus ilex. Leaf feeding with fosmidomycin, which is a specific inhibitor of the chloroplastic isoprenoid synthesis pathway, essentially stopped monoterpene emission and resulted in the decrease of the optimum temperature of photosynthetic electron transport from approximately 38 degrees C to approximately 30 degrees C. The heat stress resistance was partly restored by fumigation with 4 to 5 nmol mol(-1) air concentrations of monoterpene alpha-pinene but not with fumigations with monoterpene alcohol alpha-terpineol. Analyses of monoterpene physicochemical characteristics demonstrated that alpha-pinene was primarily distributed to leaf gas and lipid phases, while alpha-terpineol was primarily distributed to leaf aqueous phase. Thus, for a common monoterpene uptake rate, alpha-terpineol is less efficient in stabilizing membrane liquid-crystalline structure and as an antioxidant in plant membranes. Furthermore, alpha-terpineol uptake rate ( U) strongly decreased with increasing temperature, while the uptake rates of alpha-pinene increased with increasing temperature, providing a further explanation of the lower efficiency of thermal protection by alpha-terpineol. The temperature-dependent decrease of alpha-terpineol uptake was both due to decreases in stomatal conductance, g(w), and increased volatility of alpha-terpineol at higher temperature that decreased the monoterpene diffusion gradient between the ambient air (F-A) and leaf (F-I; U=g(w)\{[\}F-A - F-I]). Model analyses suggested that alpha-pinene reacted within the leaf at higher temperatures, possibly within the lipid phase, thereby avoiding the decrease in diffusion gradient, F-A-F-I. Thus, these data contribute to the hypothesis of the antioxidative protection of leaf membranes during heat stress by monoterpenes. These data further suggest that fumigation with the relatively low atmospheric concentrations of monoterpenes that are occasionally observed during warm windless days in the Mediterranean canopies may significantly improve the heat tolerance of nonemitting vegetation that grows intermixed with emitting species.
APS